Pengaruh Metode PengawetanTradisional terhadap Kadar Air pada Jenis Ikan Berbeda - Rulita Maulidya; Indria Mahgfirah; Faisal Syahputra; Azwar Thaib; Annisa Rusliana (Jurnal TILAPIA, 2024)
The aim of this research is to determine the effectiveness of traditional drying methods on several types of fish. Comparing the quality of dried fish products from drying with the SNI requirements for dried fish, looking for methods that are suitable for types of fish in traditional drying. Optimal time to produce the best quality fish. The research results showed that drying this type of fish was different from drying it under direct sunlight for 8 hours per day for 3 days. The average value of percent water content obtained ranged from 26% -32%. It was concluded that drying using traditional methods could be the right choice for drying fish.